A Multimodality Triage Algorithm to Improve Cytoreductive Outcomes in Patients Undergoing Primary Debulking Surgery for Advanced Ovarian Cancer: A Memorial Sloan Kettering Cancer Center Team Ovary Initiative - Straubhar, Alli M. (Gynecol Oncol, 2020)
OBJECTIVE: To describe outcomes using a multimodal algorithm to triage patients with advanced epithelial ovarian cancer (EOC) to primary debulking surgery (PDS) versus neoadjuvant chemotherapy (NACT). METHODS: All patients with EOC treated at our institution from 04/2015–08/2018 were identified. We included patients without contraindication to PDS who underwent prospective calculation of a Resectability (R)-score. A low risk score for suboptimal cytoreduction was defined as ≤6, and a high risk score ≥7. Patients were triaged to laparotomy/PDS, laparoscopic evaluation of resectability (LSC), or NACT depending on R-score. RESULTS: Among 299 participants, 226 (76%) had a low risk score and 73 (24%) a high risk score. For patients with a low risk score, management included laparotomy/PDS, 181 (80%); LSC, 43 (19%) (with subsequent triage: PDS, 31; NACT, 12); and NACT, 2 (1%). For patients with a high risk score, management included laparotomy/PDS, 9 (12%); LSC, 51 (70%) (with subsequent triage: PDS, 28; NACT, 23); and NACT, 13 (18%). Overall, 83% underwent PDS, with a 75% CGR rate and 94% optimal cytoreduction rate. Use of the algorithm resulted in a 31% LSC rate and a 6% rate of suboptimal PDS. CONCLUSIONS: The multimodal algorithm led to excellent surgical results; 94% of patients achieved an optimal resection, with a very low rate of suboptimal cytoreduction.